NT‐proBNP as a Mediator of the Racial Difference in Incident Atrial Fibrillation and Heart Failure. Issue 7 (2nd April 2019) - Whitman, Isaac R.; Vittinghoff, Eric; DeFilippi, Christopher R.; Gottdiener, John S.; Alonso, Alvaro; Psaty, Bruce M.; Heckbert, Susan R.; Hoogeveen, Ron C.; Arking, Dan E.; Selvin, Elizabeth; Chen, Lin Y.; Dewland, Thomas A.; et al.
Abstract : Background: Blacks harbor more cardiovascular risk factors than whites, but experience less atrial fibrillation (AF). Conversely, whites may have a lower risk of heart failure (CHF). N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) levels are higher in whites, predict incident AF, and have diuretic effects in the setting of increased ventricular diastolic pressures, potentially providing a unifying explanation for these racial differences. Methods and Results: We used data from the CHS (Cardiovascular Health Study) to determine the degree to which baseline NT‐proBNP levels mediate the relationships between race and incident AF and CHF by comparing beta estimates between models with and without NT‐proBNP. The ARIC (Atherosclerosis Risk in Communities) study was used to assess reproducibility. Among 4731 CHS (770 black) and 12 418 ARIC (3091 black) participants, there were 1277 and 1253 incident AF events, respectively. Whites had higher baseline NT‐proBNP (CHS: 40% higher than blacks; 95% CI, 29–53; ARIC: 39% higher; 95% CI, 33–46) and had a greater risk of incident AF compared with blacks (CHS: adjusted hazard ratio, 1.60; 95% CI, 1.31–1.93; ARIC: hazard ratio, 1.93; 95% CI, 1.57–2.27). NT‐proBNP levels explained a significant proportion of the racial difference in AF risk (CHS: 36.2%; 95% CI, 23.2–69.2%; ARIC: 24.6%; 95% CI, 14.8–39.6%). Contrary to our hypothesis, given an increased risk of CHF among whites in CHS (adjusted hazard ratio, 1.20; 95% CI, 1.05–1.47) and the absence of a significant association between race and CHF in ARIC (adjusted hazard ratio, 1.07; 95% CI, 0.94–1.23), CHF‐related mediation analyses were not performed. Conclusions: A substantial portion of the relationship between race and AF was statistically explained by baseline NT‐proBNP levels. No consistent relationship between race and CHF was observed. Abstract : See Editorial by Richards